American government institutions and policies - Wilson, James Q.; DiIulio, John J.; Bose, Meenekshi; Levendusky, Matthew (Cengage, 2022)
"Packed with current examples and practical insight, Wilson/Dilulio/Bose/Levendusky's AMERICAN GOVERNMENT: INSTITUTIONS AND POLICIES, 17th Edition, gives you a clear understanding of the U.S. government -- and your role in it. Highlighting emerging issues in American politics, the authors focus on the importance of governmental institutions, the historical development of governmental procedures and policies, as well as who governs in the U.S. and to what ends. New coverage includes the Trump administration, results of the 2018 and 2020 elections, the nation's response to the COVID-19 crisis, the media's role in promoting political polarization, climate change, the U.S. wealth gap, 21st century wars in Afghanistan and Iraq and more. Numerous features throughout the text help you maximize your study time, while MindTap provides you with a wealth of anywhere, anytime digital learning tools." -- (Publisher)